Bacteriological Profile and Antimicrobial Susceptibility Pattern of Isolates causing Wound Infections (Med Phoenix, 2025)
Introduction: Wound infections are a major cause of morbidity, often involving a wide range of bacterial pathogens, including multidrug-resistant organisms. Among them, Methicillin-Resistant Staphylococcus aureus (MRSA) has emerged as a significant challenge due to its resistance to commonly used antibiotics and its association with poor clinical outcomes. The rising incidence of MRSA and other resistant pathogens highlights the need for continuous surveillance. This study aims to determine the bacteriological profile and antimicrobial susceptibility patterns of wound infection isolates, with a focus on the prevalence of MRSA, to guide effective empirical therapy and inform antibiotic stewardship practices.Materials and Methods: A descriptive cross-sectional study was conducted from April 14, 2022 to August 14, 2023 in the Department of Microbiology at Shree Birendra Hospital. A total of 120 pus swab specimens were collected and processed using standard microbiological procedures. Bacterial species were identified through conventional methods, and antimicrobial susceptibility testing was conducted using the disk diffusion technique, following the Clinical and Laboratory Standards Institute (CLSI) guidelines to ensure accuracy and reliability of results.Results: Of the total bacterial isolates recovered, Gram-negative organisms accounted for 51%, while Gram-positive organisms comprised 49%, indicating a nearly equal distribution. A total of six distinct bacterial species were identified. Staphylococcus aureus emerged as the predominant isolate, representing 35% (n=42) of the total, followed by Klebsiella pneumoniae (17.5%, n=21), Escherichia coli (12.5%, n=15), and Enterobacter spp. (8.33%, n=10). Among the less frequently isolated organisms were coagulase-negative Staphylococci (5.83%, n=7) and Pseudomonas aeruginosa (4.16%, n=5). The most effective antibiotic for Gram positive organism was found to be Linezolid and the less effective was Ciprofloxacin. However, for Gram negative bacteria the most effective antibiotic was Amikacin and the less effective was Cefotaxime. Hence, the etiological agents of wound infection along with their antibiotic susceptibility pattern were determined.Conclusion: The study highlights a diverse bacteriological profile in wound infections, with a nearly equal distribution of Gram-negative and Gram-positive bacteria, and Staphylococcus aureus as the most prevalent isolate. The presence of multidrug-resistant organisms, including MRSA, underscores the urgent need for regular surveillance and adherence to antibiotic stewardship programs. Continuous monitoring of local antimicrobial susceptibility patterns is essential to guide effective empirical therapy and improve patient outcomes.